If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6i(4 + 2i) = equation (4 * 6i + 2i * 6i) = equation (24i + 12i2) = equation Solving 24i + 12i2 = aeinoqtu Solving for variable 'i'. Reorder the terms: -1aeinoqtu + 24i + 12i2 = aeinoqtu + -1aeinoqtu Combine like terms: aeinoqtu + -1aeinoqtu = 0 -1aeinoqtu + 24i + 12i2 = 0 Factor out the Greatest Common Factor (GCF), 'i'. i(-1aenoqtu + 24 + 12i) = 0Subproblem 1
Set the factor 'i' equal to zero and attempt to solve: Simplifying i = 0 Solving i = 0 Move all terms containing i to the left, all other terms to the right. Simplifying i = 0Subproblem 2
Set the factor '(-1aenoqtu + 24 + 12i)' equal to zero and attempt to solve: Simplifying -1aenoqtu + 24 + 12i = 0 Reorder the terms: 24 + -1aenoqtu + 12i = 0 Solving 24 + -1aenoqtu + 12i = 0 Move all terms containing i to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -1aenoqtu + -24 + 12i = 0 + -24 Reorder the terms: 24 + -24 + -1aenoqtu + 12i = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -1aenoqtu + 12i = 0 + -24 -1aenoqtu + 12i = 0 + -24 Combine like terms: 0 + -24 = -24 -1aenoqtu + 12i = -24 Add 'aenoqtu' to each side of the equation. -1aenoqtu + aenoqtu + 12i = -24 + aenoqtu Combine like terms: -1aenoqtu + aenoqtu = 0 0 + 12i = -24 + aenoqtu 12i = -24 + aenoqtu Divide each side by '12'. i = -2 + 0.08333333333aenoqtu Simplifying i = -2 + 0.08333333333aenoqtuSolution
i = {0, -2 + 0.08333333333aenoqtu}
| (b-5)(2b-1)=0 | | 5(x+1)-x=4x+5 | | Y(9+y)=y*9+y*y | | -(2n+2n)= | | n+1n-5=0 | | 6i(4+2i)= | | 12x^2+3x-144=0 | | 5x-2(0)=9 | | p-4p+3=0 | | 6x^2+3x-144=0 | | 7(3y-6)=21 | | -10-5x^2=-350 | | k/-9=(-9) | | X*15=4 | | p/(-3)=(-10) | | 5(-4)-2y=9 | | 2x+6x-45=9 | | -2x-32=4(x+5)-4 | | 3x+7=4(2x-2) | | 2a-3(a-5)=5 | | k-(-71)=74 | | c-78=(-10) | | 9x^2=-77+18x | | x^3-10x=-3x^2-24 | | j+4=(-85) | | -87=g-92 | | 2a-3b(a-5)=5 | | w+27=(-64) | | 2/x-22=5/x-2 | | x/7-1=2 | | m-68=-48 | | -5=j+5 |